Prevalencia de fluorosis dental en escolares de 12 años en el distrito de Cajamarca, 2016 - Sánchez Jäeger, María Elizabeth (2017)
ABSTRACT Objective: The purpose of this study was to determine the prevalence of dental fluorosis in 12-year-old schoolchildren in the district of Cajamarca, evaluating the degree of severity according to the Dean index Materials and Methods: The descriptive, transversal and observational study included a sample of 188 schoolchildren: 120 males, 68 females, out of a total of 10 educational centers chosen by simple random sampling. To evaluate the prevalence and severity of Fluorosis, the Dean index was used and the examiner was calibrated by an expert assessing the level of agreement using the Cohen Kappa index. Results : 76.1% of students had dental fluorosis with some degree of severity. There were no statistical differences in the prevalence of fluorosis and the degree of severity between both genders, with mild fluorosis predominating in both. The place of residence did not condition the prevalence or severity of fluorosis in the population studied, with the degree of mild fluorosis being the most frequent. Conclusions: It is concluded that the majority of the students of the district of Cajamarca have some degree of dental fluorosis, and there is no significant relation with gender and place of origin